The use of evidence in English local public health decision-making: a systematic scoping review - Kneale, Dylan; Rojas-García, Antonio; Raine, Rosalind; Thomas, James (Implementation science : IS, 2017)
Background Public health decision-making structures in England have transformed since the implementation of reforms in 2013, with responsibility for public health services and planning having shifted from the “health” boundary to local authority (LA; local government) control. This transformation may have interrupted flows of research evidence use in decision-making and introduced a new political element to public health decision-making. For generators of research evidence, understanding and responding to this new landscape and decision-makers’ evidence needs is essential. Methods We conducted a systematic scoping review of the literature, drawing upon four databases and undertaking manual searching and citation tracking. Included studies were English-based, published in 2010 onwards, and were focused on public health decision-making, including the utilisation or underutilisation of research evidence use, in local (regional or sub-regional) areas. All studies presented empirical findings collected through primary research methods or through the reanalysis of existing primary data. Results From a total of 903 records, 23 papers from 21 studies were deemed to be eligible and were included for further data extraction. Three clear trends in evidence use were identified: (i) the primacy of local evidence, (ii) the important role of local experts in providing evidence and knowledge, and (iii) the high value placed on local evaluation evidence despite the varying methodological rigour. Barriers to the use of research evidence included issues around access and availability of applicable research evidence, and indications that the use of evidence could be perceived as a bureaucratic process. Two new factors resulting from reforms to public health structures were identified that potentially changed existing patterns of research evidence use and decision-making requirements: (i) greater emphasis among public health practitioners on the perceived uniqueness of LA areas and structures following devolution of public health into LAs and (ii) challenges introduced in responding to higher levels of local political accountability. Conclusions There is a need to better understand and respond to the evidence needs of decision-makers working in public health and to work more collaboratively in developing solutions to the underutilisation of research evidence in decision-making.